Development of an Analytical Model of Gas Turbine to Predict the Gas Turbine Degradation - Nashreen Mhd Razali, Nashreen (Universiti Teknologi Petronas, 2008)
Degradation of gas turbine will affect the operation side of the gas power plant operator. Therefore, engine condition monitoring is important to improve safety and to reduce operation and maintenance cost of the gas turbine. In condition monitoring, the most important thing to watch is the change in engine performance trend and not the absolute values of the performance. Thus, the purpose of this project is to formulate analytical/mathematical model of gas turbine GE LM2500 to describe its thermodynamic behavior .The mathematical model is specially developed to simulate the actual trend of gas turbine performance on site by taking into account the actual composition of the working gases and the variation of the specific heats with temperature. The outputs trend of the model which are the gas generator exit temperature, the gas turbine exhaust temperature and the actual load is compared with actual outputs as monitored on site by the operators. Deviations in performance trend will indicate degradation of the gas turbine. Time plots of the compressor work and inlet filter differential pressure (DP) will help the operators to determine the right time to do corrective maintenance on the gas turbine like the water washing and inlet filter replacement